Manajemen Resolusi Konflik antara BNNP Lampung dan Publik dalam Kasus Rehabilitasi Pengurus HIPMI - Jesyka Mutiara Yuda; Muhammad Ilham; Ibrahim Besar (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
Social conflict often arises when the public perceives that the law is enforced unfairly, triggering distrust in state institutions and increasing the potential for mass escalation. This study analyzes a conflict case between the public and the Provincial National Narcotics Agency (BNNP) of Lampung concerning the decision to grant outpatient rehabilitation to several executives of the Indonesian Young Entrepreneurs Association (HIPMI) following a raid at the Grand Mercure Hotel in Bandar Lampung. Using a literature study method, this research examines the dynamics of conflict through the lenses of conflict management theory, public communication, and concept of restorative justice. The findings indicate that conflict was driven by perceptions of legal injustice, a lack of transparency in rehabilitation assessment process, irregularities in the handling of evidence, and weak institutional responses to public pressure. Based on Pondy’s stages of conflict, the incident evolved from latent conflict into manifest conflict when the public engaged in mass protests demanding consistent law enforcement. The conflict resolution analysis emphasizes the need for transparent rehabilitation procedures, accountability of law enforcement agencies, participatory dialogue between institutions and the public, and policy reforms to prevent regulatory ambiguity. Furthermore, failures in BNNP Lampung’s public communication significantly contributed to a crisis of public trust. This study concludes that conflict resolution in the context of law enforcement must integrate transparency, restorative justice, communication management, and public trust restoration to maintain social stability. The findings offer both theoretical and practical contributions to strengthening conflict resolution management within Indonesian law enforcement institutions.